Planejamento racional de fármacos baseado em produtos naturais - Montanari, Carlos Alberto; Bolzani, Vanderlan Da S. [UNESP] (My University, 2001)
In the area of drug discovery, natural products represent a myriad of templates for new lead discovery. It is, however, most unlikely that the bioactive principle itself shall become a drug; it is much more likely that a medicinal chemistry project needs to be initiated as soon the potency or selectivity or specificity of the new natural product candidate has been disclosed. Brazil has an enormous biodiversity where just a few has been disclosed. Nevertheless, it urges to initiate a joint collaboration in order to circumvent a major breakdown linking between natural products and medicinal chemistry in this country. This paper is intended to encourage people to follow up one of the most pushing forward enterprise that needs to be settled: the pharmaceutical industry.
Drug design based on natural products
Keywords: Medicinal chemistry; Natural products; Pharmaceutical industry